2016
DOI: 10.1002/oby.21516
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between weight‐related behavioral profiles and health outcomes by sexual orientation and gender

Abstract: Objective Examine relationships between weight-related factors and weight status, body dissatisfaction, chronic health conditions, and quality of life across sexual orientation and gender. Methods Two- and four-year college students participated in the College Student Health Survey (n=28,703; 2009-2013). Risk differences were calculated to estimate relationships between behavioral profiles and weight status, body satisfaction, diagnosis of a chronic condition, and quality of life, stratified by gender and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 35 publications
4
28
0
Order By: Relevance
“…Sexual minority females across both BMI categories reported more harassment and mental distress than heterosexual females of either BMI category but generally did not differ from each other. These uniformly high rates of harassment and mental distress among sexual minority females may indicate that sexual minorities remain particularly vulnerable to bullying and mental distress above and beyond other targeted groups . This pattern may also support the broader literature on the ubiquity of minority stress in the form of harassment and mental distress for sexual minority youth .…”
Section: Discussionsupporting
confidence: 60%
“…Sexual minority females across both BMI categories reported more harassment and mental distress than heterosexual females of either BMI category but generally did not differ from each other. These uniformly high rates of harassment and mental distress among sexual minority females may indicate that sexual minorities remain particularly vulnerable to bullying and mental distress above and beyond other targeted groups . This pattern may also support the broader literature on the ubiquity of minority stress in the form of harassment and mental distress for sexual minority youth .…”
Section: Discussionsupporting
confidence: 60%
“…Bankoff et al (), Cella et al (, ), and Yean et al () did not find any differences between the selected groups, whereas Gettelman and Thompson () found a lower risk of unhealthy behaviours in lesbian women. Only Katz‐Wise et al (), who recruited young volunteers, and VanKim et al (), recruiting college students, found a larger presence of disordered eating in SM women than heterosexual sample.…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, a greater body satisfaction than heterosexual women was found in SM women by Bergeron andSenn (1998), French et al (1996), Gettelman and Thompson (1993), Herzog et al (1992), Lakkis et al (1999), Moore and Keel (2003), Mor et al (2015), Owens et al (2003), Peplau et al (2008), Polimeni et al (2009), Schneider et al (1995, Siever (1994), and Strong et al (2000). Other studies did not show any significant difference as regards sexual orientation (Beren et al, 1996;Cella et al, 2010Cella et al, , 2013Davids & Green, 2011;Legenbauer et al, 2009; Nelson et al, 2011;Striegel-Moore et al, 1990;VanKim et al, 2016;Yean et al, 2013).…”
Section: Eating Disorders Symptomsmentioning
confidence: 91%
“…EDs and ED behavior are more prevalent among LGBQ+ individuals relative to heterosexual individuals. These disparities have been identified across the full spectrum of eating pathology (Bankoff, Richards, Bartlett, Wolf, & Mitchell, ; Calzo et al, ; VanKim et al, ). For example, EDs and ED behaviors are more common among men who identify as gay, bisexual or prefer an alternative identifier (Bankoff et al, ) and sexual minority women, broadly defined (Diemer et al, ) as compared to heterosexual men and women.…”
Section: Disparities Across Sexual Orientation and Their Intersectionmentioning
confidence: 98%